Planning and Implementation of Educational Institutions at PKBM Sejati Kudus - Wijayanto, Wasis; Aisy, Fadia Rohadatul; Fitriyani, Dila Eka (Lembaga Pendidikan Hikmatun Najah Blora, 2024)
This research aims to discuss (1) how the planning and implementation of learning at PKBM Sejati, (2) what are the challenges faced in the implementation of education at PKBM Sejati, and (3) how efforts to increase community trust in PKBM Sejati. PKBM as a non-formal education institution plays an important role in providing access to education for people who cannot pursue education in the formal education system. This research uses descriptive qualitative methods. The data collection techniques were interviews, observation, documentation and library studies. This research reveals that education planning at PKBM Sejati is prepared based on an analysis of community needs, so that programs are offered, such as package A, B, and C equivalency programs and trainings tailored to local needs. The implementation of education at PKBM Sejati is carried out flexibly, with an adaptive approach to the needs of students, and faces challenges such as the lack of motivation to learn from students. This research shows that although PKBM Sejati faces various obstacles, this institution still contributes significantly to increasing access to education and empowering communities through non-formal education.